2009
DOI: 10.1002/jhet.262
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crystal structure characterization of 3,5‐bis(2‐quinolyl)‐1,2,4‐triazole

Abstract: in Wiley InterScience (www.interscience.wiley.com).The first quinolyl substituted 1,2,4-triazole, 3,5-bis(2-quinolyl)-1,2,4-triazole (4), was synthesized from 2-cyanoquinoline (1) through an intermediate 2-quinolylhydrazidine (2) with 60.4% yield in a simple way. In the synthetic process of 4, another new intermediate, 1,4-diamino-1,4-bis(2-quinolyl)-2,3-diaza-1,3-butadiene (3) was obtained in a yield of 81.5%. Additionally, the absolute configurations of both 3 and 4 were determined by X-ray crystallography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…This feature is similar to that of the related substituted 4-amino-1,2,4-triazoles compounds [19,20]. The bond lengths and bond angles of 3a and 3b are similar and in normal ranges [23,26,27]. The hydrogen bonds, a C-H···π interaction and a non-bonding π···π interaction in these compounds are given in Table 4.…”
Section: Resultssupporting
confidence: 57%
“…This feature is similar to that of the related substituted 4-amino-1,2,4-triazoles compounds [19,20]. The bond lengths and bond angles of 3a and 3b are similar and in normal ranges [23,26,27]. The hydrogen bonds, a C-H···π interaction and a non-bonding π···π interaction in these compounds are given in Table 4.…”
Section: Resultssupporting
confidence: 57%
“…More interestingly, heterocyclic compounds containing 1,2,4-triazole rings can act as bridging ligands between transition metal ions thus providing rich and versatile coordination modes. For instance, iron (II) spin-crossover complexes could be used as molecular-based memory devices, displays, and switching materials [9,10]. It has also been found that the fluorine atoms and fluorine-containing groups induced into the biologically active organic compounds can greatly enhance the biological activity [11].…”
Section: Introductionmentioning
confidence: 99%